THE ROLE OF CORRECTIONAL INSTITUTIONS IN THE IMPLEMENTATION OF PRISONER DEVELOPMENT IN CLASS I CORRECTIONAL INSTITUTION SURABAYA THROUGH THE PERSPECTIVE OF LEGAL SOCIOLOGY - Margalena, Sindy; Suroso, Dr. Imam (Srawung: Journal of Social Sciences and Humanities, 2023)
The state has no right to treat a prisoner as worse or more cruel than before he or she was admitted to a prison or correctional institution. The existence of correctional institutions is needed to protect inmates against the possibility of reoffending by the inmates. Therefore, this research aims to identify several inmate development measures conducted by Class I Correctional Institution Surabaya, and to find out the implementation of the Correctional Institution’s development measures to its inmates. This type of research is empirical research combined with factual, humanitarian, and expertise approaches. Based on the research findings, it can be concluded that Class I Correctional Institution Surabaya has conducted its duties as a prisoner development institution. This can be observed from the establishment of several independence development programs, intellectual ability programs, national insight, legal awareness, and religious personality programs. However, Class I Correctional Institution Surabaya is one of the prisons that has over capacity and some constraints in implementing prisoner development. The deradicalization program is also conducted on some prisoners who were involved in terrorism crimes to change their mindset for the better.